2008
DOI: 10.1007/s11084-008-9129-2
|View full text |Cite
|
Sign up to set email alerts
|

Comments in a Discussion: Differential Rates of d- and l-tyrosine Crystallization

Abstract: We earlier reported that we had observed quantifiable differences in crystallization rates of D and L tyrosine. It has been suggested that these results were due to the presence of impurities. Here we argue that it is premature to conclude that impurities entirely explain the results. More generally, there is an accumulating weight of evidence that D and L enantiomers display unexpected differences in their physical properties and behavior. These should be taken into account as we attempt to understand the ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…For instance, it was recently seen that d - and l -tyrosine had different solubilities in water . The authors of this study reached for an extraordinary explanation, parity violating energy differences; however, Ockham would search elsewhere, and other philosophers reasonably ascribed the observations on tyrosine to undetected chiral impurities that can surely affect crystal growth and dissolution in small quantities . Similar effects may well account for the differences seen herein.…”
Section: Discussionmentioning
confidence: 56%
“…For instance, it was recently seen that d - and l -tyrosine had different solubilities in water . The authors of this study reached for an extraordinary explanation, parity violating energy differences; however, Ockham would search elsewhere, and other philosophers reasonably ascribed the observations on tyrosine to undetected chiral impurities that can surely affect crystal growth and dissolution in small quantities . Similar effects may well account for the differences seen herein.…”
Section: Discussionmentioning
confidence: 56%
“…Both [221] and [222] concluded that the discrepancy of D/L-tyrosine solubility was due to different contaminants, such as fungal spores being present in the D/L-tyrosine powders purchased from various vendors. The authors of [223] contested this interpretation, arguing that the solubility differences were due to the parity violation energy difference between enantiomers (a topic which falls outside of the scope of this review).…”
Section: Mineral-organic Interactions For Driving Enantiomeric Excessmentioning
confidence: 99%
“…Intriguingly, recent work has shown that the two might be related in that L-amino acids can also catalyse the formation of D-glyceraldehyde, and hence D-sugars, in plausible planetary environments. 6 Proposed mechanisms for the origin of biochiral specificity include the templating of organic precursors on the surfaces of non-centrosymmetric minerals such as quartz and calcite; [7][8][9] chance selection of one isomer followed by sequential replication by the resulting living process; 10 asymmetry at the central Cu ion of the complex involved in the salt-induced peptide formation reaction; 11 differential crystallization rates of D-and L-isomers, [12][13][14][15] seeding from space with non-racemic precursors [16][17][18] synthesised under conditions involving circularly polarised ultra-violet light 19,20 and even mechanisms involving possible quantum mechanical condensation phenomena at low temperature and the weak nuclear force. 21,22 There is, however, no consensus as to how such near-perfect enantiomeric separation occurred in biology and in the absence of a net chiral symmetry operator, no simple fractionation mechanism can lead to overall chiral selectivity.…”
Section: Introductionmentioning
confidence: 99%